2022
DOI: 10.3390/jcm11206138
|View full text |Cite
|
Sign up to set email alerts
|

Early Outpatient Treatment of COVID-19: A Retrospective Analysis of 392 Cases in Italy

Abstract: COVID-19 was declared a pandemic in March 2020. The knowledge of COVID-19 pathophysiology soon provided a strong rationale for the early use of both anti-inflammatory and antithrombotic drugs; however, its evidence was slowly and partially incorporated into institutional guidelines. The unmet needs of COVID-19 outpatients were taken care of by networks of physicians and researchers. We analyse the characteristics, management and outcomes in COVID-19 outpatients who were taken care of by physicians within the I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Repeated administrations (up to four or five and more) were not included in the seminal clinical trials of the vaccine makers, so the intensity and frequency of adverse events can now change in the face of an infection that has a current mortality comparable or even lower than that of flu [ 199 ]. No large human studies are available on updated mRNA products, which encode for two types of Spike proteins at the same time, regarding protection from the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated administrations (up to four or five and more) were not included in the seminal clinical trials of the vaccine makers, so the intensity and frequency of adverse events can now change in the face of an infection that has a current mortality comparable or even lower than that of flu [ 199 ]. No large human studies are available on updated mRNA products, which encode for two types of Spike proteins at the same time, regarding protection from the disease.…”
Section: Discussionmentioning
confidence: 99%
“… NEW THERAPEUTIC APPROACHES. A fourth quite relevant factor was the progressive improvement of the health response in dealing with the pandemic, with the discovery of the efficacy of certain drugs (in particular, NSAIDs but also monoclonal antibodies and appropriate use of steroids and antivirals) in preventing disease progression and the realization of the need for early intervention by doctors, even in the absence of official guidelines [ 7 , 8 , 17 22 ]. …”
Section: Lethality Trend In Italy During the Pandemic: Determining Fa...mentioning
confidence: 99%
“…Another retrospective observational study, recently released in preliminary form [ 8 ] investigated the characteristics, management and outcomes in COVID-19 patients treated in Italy by 10 volunteer physicians within the IppocrateOrg Association, between 1 November 2020 and 31 March 2021. 392 consecutive COVID-19 patients with various types of comorbidities were treated with vitamins and supplements (98.7%), aspirin (66.1%), antibiotics (62%), glucocorticoids (41.8%), hydroxychloroquine (29.6%), enoxaparin (28.6%), colchicine (8.9%), oxygen therapy (6.9%), and ivermectin (2.8%).…”
Section: Criticism Of the Ministry Guidelines By Doctors And Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID‐19 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, a disease for which several immunological and pharmacological treatments have been tried. Besides mass vaccination, early use of some pharmacological treatments including non‐steroidal anti‐inflammatory drugs (NSAIDs) has been shown to exert some protective effects against COVID‐19 (Consolaro et al, 2022 ; Cosentino et al, 2022 ; Fazio et al, 2021 ; Perico et al, 2022 ; Suter et al, 2021 ; Zamai & Rocchi, 2022 ). In this regard, a recent study reported that the rate of prescriptions of NSAIDs or paracetamol for symptomatic relief differs between non‐hospitalised and hospitalised patients (Whittaker et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%